Review of modeling and control during transport airdrop process. (2nd December 2016) - Xu, Bin; Chen, Jie
This article presents the review of modeling and control during the airdrop process of transport aircraft. According to the airdrop height, technology can be classified into high and low altitude airdrop and in this article, the research is reviewed based on the two scenarios. While high altitude airdrop is mainly focusing on the precise landing control of cargo, the low altitude flight airdrop is on the control of transport aircraft dynamics to ensure flight safety. The history of high precision airdrop system is introduced first, and then the modeling and control problem of the ultra low altitude airdrop in transport aircraft is presented. Finally, the potential problems and future direction of low altitude airdrop are discussed.